2013
DOI: 10.1111/2049-632x.12098
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic lymph node containing inactivatedTreponema pallidumcells elicits strong, antigen-specific humoral and cellular immune responses in mice

Abstract: The goal of this study was to investigate the use of a synthetic lymph node (SLN) for delivery of Treponema pallidum (Tp) antigens. Immune responses of C57BL/6 mice were analyzed at 4, 8, and 12 weeks after SLN implantation. Group 1 mice received SLN with no antigen; Group 2, SLN with formalin-inactivated Tp (f-Tp); and Group 3, SLN with f-Tp plus a CpG oligodeoxynucleotide. When tested by ELISA, sera from Group 2 and Group 3 mice showed stronger IgG antibody reactivity than sera from Group 1 mice to sonicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Fourth, efforts to develop a vaccine to prevent syphilis, and thus limit dependence on antibiotics, should be renewed. The availability of novel methods to modulate the innate and adaptive immune response, coupled with an improved understanding of T. pallidum proteogenomics, has stimulated new approaches to syphilis vaccine development [42, 43]. Advances in syphilis diagnosis, treatment, molecular surveillance and vaccines, in combination with a rapid, multi-faceted strategy for outbreak containment, would significantly benefit global public health by accelerating syphilis control efforts.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, efforts to develop a vaccine to prevent syphilis, and thus limit dependence on antibiotics, should be renewed. The availability of novel methods to modulate the innate and adaptive immune response, coupled with an improved understanding of T. pallidum proteogenomics, has stimulated new approaches to syphilis vaccine development [42, 43]. Advances in syphilis diagnosis, treatment, molecular surveillance and vaccines, in combination with a rapid, multi-faceted strategy for outbreak containment, would significantly benefit global public health by accelerating syphilis control efforts.…”
Section: Resultsmentioning
confidence: 99%
“…TP elicits antigen-specific humoral and cellular immune responses. For example, synthetic lymph nodes containing inactivated TP secrete interferon (IFN)-γ and immunoglobulin G (IgG) antibody, 12 and showed that CD4 + lymphocytes and IFN-γ predominate in local immune responses in early experimental syphilis. 13 The presence of low-level spirochetemia and immunophenotypic changes suggest monocyte activation.…”
Section: Discussionmentioning
confidence: 99%
“…Specific SIgA antigen in the local mucosa serves an important role in the early resistance to Tp infection (17). Therefore, Tp vaccines should stimulate both the systematic immunity and mucosal immunity.…”
Section: Discussionmentioning
confidence: 99%